Historical and Current Concepts of Fibrillogenesis and In vivo Amyloidogenesis: Implications of Amyloid Tissue Targeting - Kisilevsky, Robert; Raimondi, Sara; Bellotti, Vittorio (Frontiers in Molecular Biosciences, 2016)
Historical and current concepts of in vitro fibrillogenesis are considered in the light of disorders in which amyloid is deposited at anatomic sites remote from the site of synthesis of the corresponding precursor protein. These clinical conditions set constraints on the interpretation of information derived from in vitro fibrillogenesis studies. They suggest that in addition to kinetic and thermodynamic factors identified in vitro, fibrillogenesis in vivo is determined by site specific factors most of which have yet to be identified.